Slavery in plants: how the facultative hemi-parasitic plant Rhamphicarpa fistulosa can completely dominate its host - Kabiri, S.; Rodenbur, J.; Ast, A.; Bastiaans, L. (Wiley, 2017)
The rain‐fed lowland rice weed Rhamphicarpa fistulosa (Rice Vampireweed) is a facultative root parasitic plant. Growth and reproduction of R. fistulosa benefit considerably from parasitism, but how this affects the host plant is not well established. We determined accumulation and partitioning of rice–parasite biomass in two pot experiments. First, rice (cv. IR64) was grown under eight R. fistulosa densities (15–1000 seeds per pot) with two sampling times. Next, 2 parasite densities (6 and 13 plants per pot) were combined with 9 destructive samplings. Infection increased host root: shoot ratios and decreased host plant height, leaf area and tiller number. Reductions in light interception were followed by reductions in light use efficiency, causing 22–71% losses in host plant biomass and 78–100% losses in host kernel production. Parasitism eventually caused a complete standstill of host plant growth, while the parasite managed to gradually increase its share in total host plant–parasite biomass up to 50–82%. This implies that ultimately the host plant was producing solely for the sake of the parasite. Due to its facultative nature, R. fistulosa may incorrectly be perceived as relatively harmless. Upon infection this Rice Vampireweed, however, turns into a genuine slave master, whereby it completely dominates its host.